Designing a multi-parametric remote sensing framework for the identification, validation and characterization of volcanic activities in Southeast Asia - Ng, Anselm Jeng Sze (Nanyang Technological University, 2022)
Over half of the world’s active volcanoes are situated in Southeast Asia, representing an imminent yet unpredictable threat to one of the most densely populated regions in the world. Reliable volcanic surveillance is therefore essential in establishing timely and effective mitigation efforts for the region. In this regard, the application of remote sensing techniques for volcanic monitoring has experienced a surge within the past decade, in part due to its greater reliability than local sensors, which are inherently more vulnerable during eruptions based on their proximity to volcanoes. Currently, most research focuses on the evaluation of only a single remote sensing technique, where assessments of multiple techniques are much rarer. In light of this, this paper thus introduces a first-order design of a multi-parametric remote sensing framework (advisory reports, infrasound, and satellite) in the identification, validation and characterization of volcanic activity in Southeast Asia. Detection methods for each of these parameters are introduced, where they are collectively tested using various case studies (2018 Sinabung, 2018 Merapi and 2018 Salak false alarm). Results indicate that with the detection methods employed at present, the framework is robust and effective at detecting large, explosive eruptions. However, these results also highlighted potential weaknesses of the framework, especially in the detection of smaller events, where improvements were subsequently suggested for each parameter. Nonetheless, this study has provided a promising direction for remote sensing research to head in, where the field of integrating multiple techniques towards coherent eruption detection currently possesses extensive amounts of untapped potential.